The challenges of an ageing workforce: an introduction to the workforce management issues - Connell, J.; Nankervis, Alan; Burgess, J. (Routledge, 2015)
The intention of this special issue is to provide new insights into a range of the challenges facing Australia and some of our regional economic partners that have occurred due to our rapidly ageing populations and workforces. The attraction and retention of older workers have become an imperative for governments, industry managers, unions and others, in order to maximise their contributions and enable integration as well as realise the potential of both older and younger employees in the Australian and Asian labour markets. The five papers in this volume provide some valuable insights into these challenges and suggest ways of addressing them.